(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the conditions for the implementation of the policy of collectivization of agriculture in Uzbekistan, reveals the features of collectivization in the republic. Joppasi was given theoretical conclusions about the changes that occurred in the social structure of the Uzbek village as a result of collectivization.